2021
DOI: 10.1108/qae-04-2021-0060
|View full text |Cite
|
Sign up to set email alerts
|

Metrics, metrics, metrics: the emergence of technological universities in Ireland

Abstract: Purpose This paper aims to explore the experiences, attitudes and expectations of higher education managers in relation to the increased use of metrics. Specifically, the authors examine a system of metrics which was introduced as part of the process for establishing Technological Universities in Ireland. Design/methodology/approach A total of 12 managers were interviewed. The authors present data from the interviews in which the authors explore: the previous use of metrics; the impacts of the introduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Second, a series of six focus groups was conducted with students from a range of subject areas. Previous studies have reported academic managers’ perspectives (Blair, 2016; Stephens and Gallagher, 2021; Gilmore et al, 2020; Martinelli et al, 2008) or students’ experiences (Bienkowska et al, 2016; Cook-Sather et al, 2014; Cornell et al, 2013; De Groot et al, 2015; Heyler and Lee, 2014; Lee, 2008). We believe the capturing both and combining the findings adds greatly to the value of this study and that the combined key themes provide an enhanced structured from which to derive implications and recommendations.…”
Section: Methodsmentioning
confidence: 99%
“…Second, a series of six focus groups was conducted with students from a range of subject areas. Previous studies have reported academic managers’ perspectives (Blair, 2016; Stephens and Gallagher, 2021; Gilmore et al, 2020; Martinelli et al, 2008) or students’ experiences (Bienkowska et al, 2016; Cook-Sather et al, 2014; Cornell et al, 2013; De Groot et al, 2015; Heyler and Lee, 2014; Lee, 2008). We believe the capturing both and combining the findings adds greatly to the value of this study and that the combined key themes provide an enhanced structured from which to derive implications and recommendations.…”
Section: Methodsmentioning
confidence: 99%